2008
DOI: 10.1027/1864-1105.20.2.67
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Unwillingness-to-Communicate and Students’ Facebook Use

Abstract: A survey with 172 students was conducted at a large southern research university to examine how unwillingness-to-communicate in interpersonal communication influences gratifications sought and gratifications obtained from Facebook use. The study investigated the relationship between two dimensions of unwillingness-to-communicate (approach-avoidance and reward) and different motives of Facebook use. In addition, it examined the relationship between unwillingness-to-communicate and the behavioral and attitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
270
1
16

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(338 citation statements)
references
References 30 publications
(61 reference statements)
33
270
1
16
Order By: Relevance
“…Sheldon [19] found that (in terms of Facebook use) people who are more involved in online relationships are those who are willing to communicate in real life. Lu and Hsiao [14] found that extraverts think more highly of the social value of SNS than do introverts.…”
Section: Loneliness and Sns Usagementioning
confidence: 99%
“…Sheldon [19] found that (in terms of Facebook use) people who are more involved in online relationships are those who are willing to communicate in real life. Lu and Hsiao [14] found that extraverts think more highly of the social value of SNS than do introverts.…”
Section: Loneliness and Sns Usagementioning
confidence: 99%
“…This is an example of the homophily principle, which states that people with related attributes, such as age, interests, and personality, form similar ties [75]. Analyses of [76][77][78][79][80] are just additional examples of the excellent body of work carried out by researchers in order to better understand the existing correlation between personality and social media platforms.…”
Section: Social Media Platforms As Sources To Deriving Personality Trmentioning
confidence: 99%
“…Erdoğan (2008) in his study found that increased Internet usage and Internet attitudes were related to Turkish adolescents' loneliness. On the other hand, Sheldon (2008) examined the relationship between unwillingness to communicate in interpersonal communication and Facebook use; she found people who were willing to communicate in social settings were also the ones who were active in online relationships. Miyata and Kobayashi (2008) found in their studies that people's abundance of social ties increases their use of personal computers and mobile phones for e-mailing them.…”
Section: The Rich Gets Richer Vs the Poor Gets Richer Hypothesismentioning
confidence: 99%